Density distribution profile for internodes and nodes of Phyllostachys edulis (Moso bamboo) by computer tomography scanning. (15th September 2015) - Huang, Puxi; Chang, Wen-Shao; Ansell, Martin P.; Chew, Y.M. John; Shea, Andy
Highlights: This study measured the density of Moso Bamboo in 3 directions by CT-scanning. This study aimed to provide density database of Moso bamboo for heat transfer simulation. Both internodes and nodes parts of Moso bamboo culms were measured. The greyscale values of CT-scanned images were utilised for calculating the density of Moso bamboo. The different proportions and growing pattern of the vascular bundles tissues and the parenchyma ground tissues are the main reason of the density variation. Abstract: This study aims to quantify the density distribution, and specify the density distribution difference between internodes and nodes parts of Phyllostachys edulis (Moso Bamboo) in the radial, tangential and longitudinal directions. Due to the anatomical complexity of Moso bamboo, the measurement methods of bulk density are insufficient. In this work, Computed Tomography (CT) scanning has been selected to quantify the density distribution of Moso bamboo. Major findings from both anatomical analysis and CT scanning quantifications are that the Moso bamboo density of the internodes parts and the nodes parts reduce from the external surface to the internal surface of the culm wall in the radial direction. In the longitudinal direction, the internode parts of the Moso bamboo have relatively uniform density. Significant density fluctuation variations occur at the nodes parts of the Moso bamboo. The different proportions of the vascular bundles tissues and the parenchyma ground tissues dominate the density variation of the Moso bamboo in the radial direction. In the longitudinal direction, relatively uniform density of the internodes parts of the Moso bamboo is attributed to the straight vascular bundles. The significant density variation in the node parts is caused by the irregular intertwined vascular bundles.